The Effect of Media Video Practicum Based on Scientific on Ability Students' Critical Thinking in Class VII Junior High School - Ginting, Syahfitriani Br; Sri HANIPAH; Herrio Tekdi NAINGGOLAN; Rival HANIP; Yani AMENDA (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This study seeks to determine how a media video practicum based on science affects students' capacity for critical thought in class VII Junior High School 4 Satu Atap Barusjahe. Quasi-experimental research using a research design is the method used. the non-equivalent control group design for the pretest and posttest. This research’s subject is Junior High-class VII-A (Control Class/ 32 students), and class VII-B (Eksperimen Class/ 32 students). The data collection technique used a pretest and posttest. The data analysis used inferential statistics and parametric descriptive and used IBM SPSS Statistic 26. Results of posttest ability students’ critical thinking are (2,659) > (1,677), showing that there are differences in the ability of students' critical thinking. When comparing the ability of students’ critical thinking in the experiment class to the control class, it can be said that the media video practicum's impact on the ability of students’ critical thinking was much greater.